2002
DOI: 10.1124/mol.62.6.1373
|View full text |Cite
|
Sign up to set email alerts
|

A3Adenosine Receptors in Human Astrocytoma Cells: Agonist-Mediated Desensitization, Internalization, and Down-Regulation

Abstract: A 3 adenosine receptor activation has been previously demonstrated to result in both neuroprotective and neurodegenerative effects, depending upon specific pathophysiological conditions. This dual effect may depend on receptor regulation mechanisms that are able to change receptor availability and/or function. In the present study, we investigated desensitization, internalization, and down-regulation of native A 3 adenosine receptors in human astrocytoma cells after exposure to the agonist 2-chloro-N6-(3-iodob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 38 publications
1
68
1
Order By: Relevance
“…Studies using CHO cells stably expressing the A 3 receptors have demonstrated that, following a few minutes of exposure to the agonist, there is rapid phosphorylation of the A 3 receptor, a reduction in number of A 3 high affinity agonist binding sites [16], and receptor internalization [19]. In human astrocytoma cells, brief exposure (1-60 min) to nanomolar concentrations of Cl-IB-MECA results in a rapid uncoupling of A 3 receptors and receptor internalization while a long-lasting (1-24 h) Cl-IB-MECA treatment leads to receptor down-regulation which recovers after several hours [20]. On this basis, in our experiments, 9 to 15 min of treatment with Cl-IB-MECA likely produces uncoupling and internalization of the A 3 receptor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies using CHO cells stably expressing the A 3 receptors have demonstrated that, following a few minutes of exposure to the agonist, there is rapid phosphorylation of the A 3 receptor, a reduction in number of A 3 high affinity agonist binding sites [16], and receptor internalization [19]. In human astrocytoma cells, brief exposure (1-60 min) to nanomolar concentrations of Cl-IB-MECA results in a rapid uncoupling of A 3 receptors and receptor internalization while a long-lasting (1-24 h) Cl-IB-MECA treatment leads to receptor down-regulation which recovers after several hours [20]. On this basis, in our experiments, 9 to 15 min of treatment with Cl-IB-MECA likely produces uncoupling and internalization of the A 3 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Because it has been demonstrated that A 3 adenosine receptors undergo a rapid desensitization that is more evident and persistent when the agonist is applied for long periods [20], we chose to examine a different protocol, shortening the time of Cl-IB-MECA application. As shown in Fig.…”
Section: Selective Stimulation Of Adenosine a 3 Receptors By A Short mentioning
confidence: 99%
See 1 more Smart Citation
“…Jurkat cells were processed for electron microscopy immunocytochemistry as described previously (Trincavelli et al, 2002) using a rabbit polyclonal anti-PBR antibody (Trevigen) diluted 1:10 in PBS containing 0.1% gelatin and 0.5% bovine serum albumin. Negative controls were performed in the absence of anti-PBR antibody.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to know how these agonists and antagonists behave in A 3 AR-mediated pathways that are independent of G proteins, such as arrestin. The A 3 AR has been reported to be a rapidly desensitizing receptor [10,11], and receptor regulation appears to be important in the clinical actions of A 3 AR agonists [12]. GRKs have been suggested to be involved in the desensitization and internalization process.…”
Section: Introductionmentioning
confidence: 99%